2003
DOI: 10.1063/1.1585117
|View full text |Cite
|
Sign up to set email alerts
|

Apertureless near-field optical microscopy: A study of the local tip field enhancement using photosensitive azobenzene-containing films

Abstract: The local optical field enhancement which can occur at the end of a nanometer-size metallic tip has given rise to both increasing interest and numerous theoretical works on near-field optical microscopy. In this article we report direct experimental observation of this effect and present an extensive study of the parameters involved. Our approach consists in making a “snapshot” of the spatial distribution of the optical intensity in the vicinity of the probe end using photosensitive azobenzene-containing films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…Ultrahigh-resolution fluorescence microscopy utilizing two-photon excitation and sharp metal tips and spectroscopy of single molecules have been demonstrated using similar configurations [92]. Direct observations of the enhanced field using photosensitive films have confirmed the nanoscopic spatial confinement of the electric field, hence excluding the possibility of surface modification due to the tip expansion [91]. The favorable sharp tip geometry (leading to the lightning rod effect discussed earlier) and the multiple scattering between the resonantly coupled probe tip and the sample structure thus effectively lead to the focusing of the optical power by collecting over the larger, nearly flat probe surface and reradiating over the smaller and sharper tipapex structure.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Ultrahigh-resolution fluorescence microscopy utilizing two-photon excitation and sharp metal tips and spectroscopy of single molecules have been demonstrated using similar configurations [92]. Direct observations of the enhanced field using photosensitive films have confirmed the nanoscopic spatial confinement of the electric field, hence excluding the possibility of surface modification due to the tip expansion [91]. The favorable sharp tip geometry (leading to the lightning rod effect discussed earlier) and the multiple scattering between the resonantly coupled probe tip and the sample structure thus effectively lead to the focusing of the optical power by collecting over the larger, nearly flat probe surface and reradiating over the smaller and sharper tipapex structure.…”
mentioning
confidence: 73%
“…Several investigators have attempted to explain the physical phenomena responsible for surface nanostructuring [89][90][91]. In general, material removal by ablation can be associated with photothermal, photomechanical, and photochemical effects.…”
Section: Apertureless Nsom Based Nanomachiningmentioning
confidence: 99%
See 1 more Smart Citation
“…• Several theoretical works (e. g. Novotny et al, 1997;Martin and Girard, 1997) and experiments (e.g., Aigouy et al, 1999;H'Dhili et al, 2001;Bachelot et al, 2003, Bouhelier et al, 2003 have showed that the end of apertureless metal tip can present an electromagnetic singularity resulting in a strongly confined nano-source. This effect possibly involves local second harmonic generation or white light emission.…”
Section: Apertureless Near-field Optical Microscopy Promising Approacmentioning
confidence: 99%
“…This is due to the high density of charges at the apex that interact with the illumination field to create enhanced evanescent fields confined near the probe [85]. As a result, this opens an entirely new dimension to SNOM, in that spectroscopies can be performed on nanostructures with advantages over conventional aperture-based methods.…”
Section: Metal Tips For Illumination Mode Imaging Through Tip Field Ementioning
confidence: 99%